Computer-Assisted Percutaneous Scaphoid Fixation: Concepts and Evolution - Smith, Erin J.; Ellis, Randy E.; Pichora, David R. (Journal of Wrist Surgery, 2013)
Background The treatment for undisplaced scaphoid waist fractures has evolved from conventional cast immobilization to percutaneous screw insertion. Percutaneous fixation reduces some of the risks of open surgery, but can be technically demanding and carries the risk of radiation exposure. Recently, computer-assisted percutaneous scaphoid fixation (CAPSF) has been gaining interest.Materials and Methods Conventional percutaneous scaphoid fixation is performed under fluoroscopic guidance and involves insertion of a guide wire along the length of the scaphoid to facilitate placement of a cannulated screw. Adapting computer-assisted techniques for scaphoid fixation poses several unique challenges including patient tracking and registration.Results To date, five groups have successfully implemented systems for CAPSF. These systems have implemented wrist immobilization strategies to resolve the issue of patient tracking and have developed unique guidance techniques incorporating 2D fluoroscope, cone-beam CT, and ultrasound, to circumvent patient-based registration.Conclusions Computer-aided percutaneous pinning of scaphoid waist fractures can significantly reduce radiation exposure and has the potential to improve the accuracy of this procedure. This article reviews the rationale for, and the evolution of, CAPSF and describes the key principles of computer-assisted technology.
Keywords: scaphoid; fracture; internal fixation; percutaneous fixation; computer-assisted surgery